Flower colour and flowering phenology mediate plant–pollinator interaction assembly in a diverse co‐flowering community. (30th July 2022) - Albor, Cristopher; Ashman, Tia‐Lynn; Stanley, Amber; Martel, Carlos; Arceo‐Gómez, Gerardo
Abstract: Uncovering the role of competition and facilitation in community assembly is central for developing a predictive understanding of the forces that organize biodiversity. Standard trait‐based approaches however rely on detection of only one assembly mechanism (competition or facilitation) along a single trait even though pollinator‐mediated plant–plant interactions can be structured along multiple phenotypic, phenological and ecological traits. We evaluated plant species distribution along multiple phenotypic and ecological traits (flower colour, flowering time, pollinator sharing) and described an entire co‐flowering community as a set of modules with unique patterns of assembly, to test predictions regarding the relative contribution of competition and facilitation to the assembly of a diverse co‐flowering community. We show a modular pattern of flower colour assembly. Flower colour modules differ in their spectral reflectance patterns including colour hue and saturation. Within modules, however, species are differentially assembled along phenological and ecological traits (pollinator sharing) depending on the main pollinator group visiting plant species within each module. Results suggest different trait assembly patterns within individual trait‐modules in the same co‐flowering community and that different trait‐patterns can result from the same type of ecological interaction. This study reveals empirical evidence of community assembly along multiple axes of trait differentiation and raises caution when interpreting assembly patterns based on a single trait. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.